Simulation of the Grondona system of conditional currency convertibility based on primary commodities, considered as a means to resist currency crises - Patrick Collins; Jameel Ahmed; Ahamed Kameel Mydin Meera (Journal of Risk and Financial Management, 2019)
Currency crises are a significant feature of the present-day world economy, in which financial transactions are many times larger than monetary flows in the "real economy", so that defending a currency's exchange-rate is a major challenge for the governments of countries which may be smaller than a single large corporation. It is made even more difficult due to the United States government and its agents openly using economic pressures to try to force other countries to obey its orders, even including regime change. Guaranteed convertibility of a currency, such as maintaining a gold standard, can in principle help to stabilise its value, but this has been absent since the end of US dollar convertibility in 1971. The Grondona system of conditional currency convertibility was not planned as a counter-measure for currency crises. However the simulation of its operation demonstrated in this paper shows clearly how its automatic counter-cyclical stock-holding in response to movements in commodity prices-and so to exchange-rate movements that alter domestic commodity prices-causes monetary flows that would resist large exchange-rate movements (among other effects), and thereby tend to ameliorate a currency crisis. Moreover, it would achieve this without the need for international negotiations, agreements or other geopolitical trade-offs.
Keywords: 330; Grondona system; currency convertibility; commodity price stabilisation; currency crisis